Ślady orygenizmu w "Diversarum hereseon liber" Filastriusza z Brescii - Szram, Mariusz (Vox Patrum, 2025)
The purpose of the article is answering the question of whether or not Philastrius of Brescia, the author of the catalog of heresies Diversarum hereseon liber, included in his treatise allusions to the ideas of Origen or any such circulating under his name and if he has indeed mentioned them – how he evaluated them. It is interesting to examine not only allusions to the debatable ideas of Alexandrian, but also positive inspirations by the theological thought of Origen as a pioneer in laying the foundations of Christian theology. An important research problem is also the attitude of the Bishop of Brescia to allegorical exegesis, of which Origen was the main representative. The conclusions of the presented comparative analysis of the source material are as follows: 1) the treatise of Philastrius lacks named references to the person and works of Origen; 2) there are, however, indirect references to various origenian ideas, and they are present both in the descriptions of heresy and in the lecture of the orthodox doctrine of the faith; 3) the catalog of the Bishop of Brescia explicitly condemns the doctrine of the preexistence of souls, while there is no mention of the theory of apocatastasis; 4) Philastrius’ criticism mainly concerns the views of Origen in the extreme or includes ideas attributed to him, but about which there is no certainty that he actually recognized them in that form; while some formulations, coming from the Alexandrian himself, are met with acceptance by the author of the catalog; 5) with regard to the issues related to allegorical exegesis of the Old Testament, Philastrius represents a thinking on biblical Christocentrism similar to Origen and his followers.